INDUKSIKALUS DAN REGENERASI TUNAS PULAI PANDAK (Rauwolfta serpentina L.) - Yunita, Rossa; Lestari, Endang Gati (BERITA BIOLOGI, 2008)
In vitro culture can be applied for producing new genotype which is tolerant to biotic and abiotic or to incerase secondary metabolic content. To obtain the optimum result of variety improvement, regeneration system should firstly be found out.It is sufficiently difficult to regenerate pulai pandak (Rauwolfia serpentina L.). Hence, with this system, the improvement of R. serpentina with secondary metabolic content higher than the other. The mother stok of R. serpentina used in this experiment, belongs to the collection of BB-Biogen. Calli were produced from leaves and internodes which is cultured at medium MS contain 2.4-D (0, 1, 3,5, 7 mg/1) combined with caseine hydrolysate 3 mg/1. Regeneration medium was MS contain BA (0,5, 1 mg/1) combined with zeatin (0, 0.1 and 0.5 mg/1) and root formation used was three kinds of auxin (IBA, IAA and NAA). The result showed that inter nodels was better that leaves to callus induction. In this experiment, MS + 2,4-D 1 mg/1 + CH 3 mg/1 was the best medium to induct calli,while medium MS + BA 1 mg/1 + Zeatin 0,5 mg/1 + maltosa 3% to regenerate and MS + IBA lmg/1 for root induction.